Answer:
AGREE!
Step-by-step explanation:
"I agree with Lin, she used the correct formula to get this answer"
1st box:
m<A + m<B + m<C = 180
2nd box:
substitution property
3rd box:
division property of equality
Hope it helps.
Answer:
The answer is B
Step-by-step explanation:
Answer: the height of the pole is 16.1 m.
Step-by-step explanation:
The scenario is illustrated in the attached photo.
x represents the height of the pole.
y represents the distance from the foot of one stabilizing wire to the foot of the pole.
30 - y represents the distance from the foot of the other stabilizing wire to the foot of the pole.
In solving the triangles, we would apply the tangent trigonometric ratio which is expressed as
Tan θ, = opposite side/adjacent side.
Considering triangle ACD,
Tan 60 = x/y
x = ytan60 = y × 1.732
x = 1.732y- - - - - - - - -1
Considering triangle BCD,
Tan 38 = x/(30 - y)
x = (30 - y)tan38 = 0.781(30 - y)
x = 23.43 - 0.781y- - - - - - - - -2
Substituting equation 1 into equation 2, it becomes
1.732y = 23.43 - 0.781y
1.732y + 0.781y = 23.43
2.513y = 23.43
y = 23.43/2.513
y = 9.3
x = 1.732y = 1.732 × 9.3
x = 16.1 m
Answer:
The quotient is 3x - 11 + 60/(x + 5) ⇒ 2nd answer
Step-by-step explanation:
* We will use the long division to solve the problem
- The dividend is 3x² + 4x + 5
- The divisor is x + 5
- The quotient is the answer of the division
- If the divisor not a factor of a dividend, the quotient has
a remainder
* Lets solve the problem
- At first divide the first term in the dividend by the first term in
the divisor
∵ 3x² ÷ x = 3x
- Multiply the divisor by 3x
∴ 3x (x + 5) = 3x² + 15x
-Subtract this expression from the dividend
∴ 3x² + 4x + 5 - (3x² + 15x) = 3x² + 4x + 5 - 3x² - 15x = -11x + 5
- Divide the first term -11x in the new dividend by the first
term x in the divisor
∴ -11x ÷ x = -11
- Multiply the divisor by -11
∴ -11(x + 5) = -11x - 55
-Subtract this expression from the new dividend
∴ -11x + 5 - (-11x - 55) = -11x + 5 + 11x + 55 = 60
∴ The quotient is 3x - 11 with remainder = 60
* The quotient is 3x - 11 + 60/(x + 5)